Spinal reconstruction for osteomyelitis with free vascularized fibular grafts using intra‐abdominal recipient vessels: A series of three cases. Issue 7 (6th September 2013) - Aliano, Kristen A.; Agulnick, Marc; Cohen, Benjamin; Gonya, Gary; Low, Christopher; Stavrides, Steve; Addona, Tommaso; Goncalves, John; Shin, David; Kilgo, Matthew S.; Davenport, Thomas A.
<x xml:space="preserve">Abstract</x> Reconstruction of bony defects in the surgical management of vertebral osteomyelitis is a challenging endeavor. Our objective is to report the use of intra‐abdominal vessels as the recipient vessels for microanastomosis of vascularized bone graft and the use of a spinal cage for fixation. Three patients failed conservative treatment for vertebral osteomyelitis and suffered pathologic fracture. Their treatment consisted of staged posterior irrigation and debridement with segmental fixation, followed by a thoracoabdominal approach multiple‐level corpectomy. Reconstruction was performed with a free vascularized fibular graft placed within a custom, expandable cage. The vascularized fibular graft was anastomosed to an intra‐abdominal recipient vessel. All patients improved clinically with no neurologic deficits noted. All showed evidence of successful fusion. Free vascularized bone grafts continue to be an excellent option for multi‐level spinal defects related to osteomyelitis. Intra‐abdominal recipient vessels are appropriate recipient vessels, as their diameter, length, and accessibility allow vascularized bone graft reconstruction of vertebral column defects of the thoracolumbar region. These vessels are also easily accessible and the anastomoses can be performed in the superficial operating incision. © 2013 Wiley Periodicals, Inc. Microsurgery 33:560–566, 2013.